Design and experimental analysis of a dual‐cavity high‐concentration adaptive passive micro direct methanol fuel cell - Zuo, Kaiyuan; Yuan, Zhenyu (International journal of energy research, 2021)
Summary In this article, a high concentration adaptive direct methanol fuel cell based on a dual‐cavity structure is presented. The performance of the cell is investigated experimentally under different supply concentrations of methanol solution to detect the optimal working conditions. The advantages of the anode double‐cavity structure in high concentration and high energy density fuel supply are proved. The effects of stainless steel metal felt, plastic porous barrier layer, hydrophilic and hydrophobic filter membrane on cell performance are experimentally investigated. A high concentration adaptive direct methanol fuel cell based on a dual‐cavity structure is presented. The advantages of the anode double‐cavity structure in high concentration and high energy density fuel supply are proved.